Integrated Pharmacogenetics Analysis of the Three Fangjis Decoctions for Treating Arrhythmias Based on Molecular Network Patterns - Wei, Penglu; Long, Dehuai; Tan, Yupei; Xing, Wenlong; Li, Xiang; Yang, Kuo; Liu, Hongxu (Frontiers in Cardiovascular Medicine, 2021)
Abstract Aim: To explore the diverse target distribution and variable mechanisms of different fangjis prescriptions when treating arrhythmias based on the systems pharmacology. Methods: The active ingredients and their corresponding targets were acquired from three fangjis (ZT, GLT and HET), and the arrhythmia-related genes were identified based on comprehensive database screening. Network were constructed between the fangjis and arrhythmia and used to define arrhythmia modules. Common and differential gene targets were identified within the arrhythmia network modules, and the cover rate (CR) matrix was applied to compare the contributions of the fangjis to the network and modules. Comparative pharmacogenomic analyses were then conducted to difine the arrhythmia-related signaling pathways regulated by fangjis prescriptions. Finally, the divergence and convergence points of the arrhythmia pathways were deciphered based on databases and the published literature. Results: A total of 187, 105 and 68 active ingredients, and 1139, 1195 and 811 corresponding gene targets of the three fangjis were obtained, and 102 arrhythmia-related genes were acquired. An arrhythmia network was constructed and sub-divided into 4 modules. For the target distribution analysis, 65.4% of genes were regulated by three fangjis within the arrhythmia network. ZT and GLT were more similar to each other, mainly regulated by module 2, whereas HET was divided among all modules. From the perspective of signal transduction, calcium-related pathways (calcium, cGMP-PKG, cAMP), and endocrine system-related pathways (oxytocin signaling pathway and renin secretion pathways) were associated with all three fangjis prescriptions. Nevertheless, heterogeneity existed between the biological processes and pathway distribution among the three prescriptions. GLT and HET were particularly inclined towards the conditions involving abnormal hormone secretion, whereas ZT tended towards RAAS disorders. However, calcium signaling-related pathways prominently feature in the pharmacological activities of the decoctions. Conclusion: Comparing the various distributions of the three fangjis and pathways provide evidence regarding precise applications towards individualized arrhythmia treatments.